Multi-route transmission potential of SARS-CoV-2 in healthcare facilities - Feng, Baihuan; Xu, Kaijin; Gu, Silan; Zheng, Shufa; Zou, Qianda; Xu, Yan; Yu, Ling; Lou, Fangyuan; Yu, Fei; Jin, Tao; Li, Yuguo; Sheng, Jifang; et al. (Journal of hazardous materials, 2021)
[Display omitted] •SARS CoV-2 was detected in 5.5 % of all samples collected.•Nosocomial transmission of SARS-CoV-2 is potential to occur via multiple routes.•The transmission dynamics of SARS-CoV-2 differ from those of SARS-CoV.•Disinfection practices and personal hygiene is essential to reduce virus transmission. Understanding the transmission mechanism of SARS-CoV-2 is a prerequisite to effective control measures. To investigate the potential modes of SARS-CoV-2 transmission, 21 COVID-19 patients from 12–47 days after symptom onset were recruited. We monitored the release of SARS-CoV-2 from the patients’ exhaled breath and systematically investigated environmental contamination of air, public surfaces, personal necessities, and the drainage system. SARS-CoV-2 RNA was detected in 0 of 9 exhaled breath samples, 2 of 8 exhaled breath condensate samples, 1 of 12 bedside air samples, 4 of 132 samples from private surfaces, 0 of 70 samples from frequently touched public surfaces in isolation rooms, and 7 of 23 feces-related air/surface/water samples. The maximum viral RNA concentrations were 1857 copies/m3 in the air, 38 copies/cm2 in sampled surfaces and 3092 copies/mL in sewage/wastewater samples. Our results suggest that nosocomial transmission of SARS-CoV-2 can occur via multiple routes. However, the low detection frequency and limited quantity of viral RNA from the breath and environmental specimens may be related to the reduced viral load of the COVID-19 patients on later days after symptom onset. These findings suggest that the transmission dynamics of SARS-CoV-2 differ from those of SARS-CoV in healthcare settings.